Reutilização do substrato e concentração da solução nutritiva no cultivo do tomateiro do grupo salada - Melo, Danilo Mesquita [UNESP] (2015)
The substrate and the nutrient solution are components inherent of open hydroponic systems which directly influence on performance of plants. Knowledge of the changes occurring in organic substrates, together with the management of nutrient solution, can provide information to assist the tomato cultivation in coconut husk fiber. Therefore, it aimed with this work to evaluate the reuse of the substrate due to the concentration of the nutrient solution in the cultivation of tomato salad group. The Paronset hybrid was cultivated in coconut husk fiber substrate, fertigated with recommended nutrient solution. The plants grew in three levels of use of the substrate (new substrate, reused once and reused twice) and five concentrations of nutrient solution (25%, 50%, 100%, 150% and 200% of the recommended concentration). Evaluations consisted in chemical and physical characterization of the substrate after the harvest, yield and qualitative characteristics of fruits and nutritional status of plants. Only there was interaction between substrate utilization and concentration of the nutrient solution for the density of the substrate. The productivity and the mass of fruit reduced to the second reuse of the substrate. The use of 96% solution concentration provided higher productivity. The largest fruit weight was obtained with 25% solution concentration. The nutritional status of tomato is not changed due to the use of the substrate. The concentration of the nutrient solution affects the nutritional status of tomato